Studying the electrochemical behaviors of anodized metallic implants for improved corrosion resistance - USTA, AYBALA (My University, 2022)
A study about long-term corrosion behavior of anodized and nonanodized Ti6Al4V and MgAZ31B biomaterials was conducted under controlled conditions. By applying 20V DC potential, MgAZ31B alloys was anodized in phosphoric acid and potassium hydroxide while Ti6Al4V alloys was anodized in phosphoric acid and oxalic acid. Long-term experiments were carried out by immersing them in deionized (DI) water, 3% NaCl and phosphatebuffered saline (PBS) solutions. The corrosion rate and pattern were measured by electrochemical analysis. Also, as a result of anodization, the natural oxide layer was observed on the material surface, thus the corrosion rate is reduced and the life of the biomaterial has been improved.

Eloksallı ve anodize edilmemiş Ti6Al4V ve Mg AZ31B biyomalzemelerinin korozyon davranışına ilişkin uzun vadeli bir araştırma, kontrollü koşullar altında gerçekleştirilmiştir. Ti6Al4V fosforik asit ve oksalik asit içinde anodize edilirken, Mg AZ31B fosforik asit ve potasyum hidroksit içinde 20V DC potansiyel uygulanarak anodize edilmiştir. %3 NaCl, fosfat tamponlu salin (PBS) ve deiyonize (DI) su çözeltilerine daldırılarak uzun süreli deneyler yapıldı. Korozyon hızı ve deseni elektrokimyasal analiz ile ölçülmüş ve anotlamanın malzeme yüzeyindeki doğal oksit tabakasını arttırdığı, korozyon hızını azalttığı ve biyomalzemenin ömrünü uzattığı gözlemlenmiştir
Gelişmiş korozyon direnci için eloksallı metalik implantların elektrokimyasal davranışlarının incelenmesi
Keywords: Anodization; corrosion; electrochemical behavior; metallic biomaterials; Anotlama; elektrokimyasal davranış; korozyon; metalik biyomalzemeler